2007
DOI: 10.1017/s0144686x07006083
|View full text |Cite
|
Sign up to set email alerts
|

Veiled entrapment: a study of social isolation of older Chinese migrants in Brisbane, Queensland

Abstract: This paper presents the findings of a study of the support and service needs of older Chinese people in Brisbane, the capital city of Queensland, Australia. There were two specific objectives: to ascertain the problems encountered by older Chinese-Australians in their daily lives and social activities; and to develop policy and service development recommendations, with a view to mitigating their problems, meeting their unmet needs, improving their quality of life, and enhancing their participation in Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
127
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 30 publications
13
127
1
Order By: Relevance
“…By cross-comparing the results of our pilot survey with data generated from the Families and Migration: Older People from South Asia study we examined the robustness of our findings across two specific sub-groups: the Indian and Bangladeshi populations. Furthermore, as loneliness has emerged consistently as a theme from qualitative studies with a range of diverse migrant communities we would argue that it is a concept that is understood and experienced by these groups and, more broadly, is a universal experience and an integral component of the human condition (Ip et al 2007). The challenge for researchers operating within a multi-cultural/multi-lingual environment is to find the vocabulary and questions that can tap into this universal human experience.…”
Section: Discussionmentioning
confidence: 98%
“…By cross-comparing the results of our pilot survey with data generated from the Families and Migration: Older People from South Asia study we examined the robustness of our findings across two specific sub-groups: the Indian and Bangladeshi populations. Furthermore, as loneliness has emerged consistently as a theme from qualitative studies with a range of diverse migrant communities we would argue that it is a concept that is understood and experienced by these groups and, more broadly, is a universal experience and an integral component of the human condition (Ip et al 2007). The challenge for researchers operating within a multi-cultural/multi-lingual environment is to find the vocabulary and questions that can tap into this universal human experience.…”
Section: Discussionmentioning
confidence: 98%
“…Due to a lack of large-scale survey data among older migrant populations, only qualitative research and some small-scale quantitative studies on their subjective well-being have been conducted so far (e.g. Dong et al 2012;Emami and Ekman 1998;Ip et al 2007;Treas and Mazumdar 2002;Victor et al 2012). Outcomes of these studies largely confirm the general idea that low socioeconomic status and poor health are main determinants of loneliness amongst older migrants, apart from some group-specific, risk-enhancing factors like homesickness, missing family and friends left behind, language and cultural barriers and experiences with racial discrimination, stigmatisation and other negative reactions from the outside world.…”
Section: Introductionmentioning
confidence: 99%
“…Attempting to identify the factors that contribute to social isolation and reduced well-being, researchers have pointed to the lack of social and emotional support that migrants experience in their new home country (Abbott et al, 2003; Park & Kim, 2013). In particular, aside from barriers to participation associated with culture and language (Ip, Lui, & Chui, 2007; Westcott & Vazquez Maggio, 2015), it has been suggested that poor health and limitations in mobility and independence make it difficult for older migrants to shape their life in ways they wish (Meijering & Lager, 2014). As a result, even among those who have lived in the host country for many years, older migrants may still have less access to social support networks compared with their older non-migrant counterparts (Park & Kim, 2013).…”
mentioning
confidence: 99%